Profitabilitas, Pertumbuhan Penjualan dan Arus Kas Operasi Terhadap Financial Distress pada Perusahaan Sub Sektor Batu Bara yang Terdaftar di BEI periode 2019-2023 - Charismadwita Charismadwita; Nita Astuti (BISMA : Business and Management Journal, 2026)
Identifying financial distress conditions is crucial because it can serve as an early warning system before bankruptcy occurs. This study aims to analyze the effect of profitability, sales growth, and operating cash flow on financial distress in coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The sampling technique used was purposive sampling, with 20 companies as the sample. The research method used was a quantitative approach with secondary data obtained through the company's financial statements. The data analysis technique used was panel data regression and statistical programs using Eviews 12. The results showed that profitability had an effect on financial distress (Prob. 0.0000 <0.05) and sales growth had an effect on financial distress (Prob. 0.0085 <0.05), while operating cash flow had no effect on financial distress (Prob. 0.6652 >0.05). Simultaneously, the variables of profitability, sales growth, and operating cash flow had an effect on financial distress (Prob(F-statistic) of 0.000000 <0.05). It is hoped that these findings can be used as consideration for company management and investors in making decisions related to the company's financial condition.